Collaborative Governance and the Challenges of Network-Based Research. Issue 8 (November 2020) - Berardo, Ramiro; Fischer, Manuel; Hamilton, Matthew
We review the literature examining collaborative governance processes from a network perspective and evaluate the extent to which it tackles important conceptual and methodological challenges. In particular, we assess whether scholars clearly identify the boundaries of the network, define nodes and the nature of ties, and examine how they deal with missing data, account for tie strength, take tie multiplexity into account, and study networks over time. We discuss the implications of our findings for the collaborative governance literature and ways to address the shortcomings in existing research.